Pelatihan Inovasi Media Pembelajaran Literasi dan Numerasi Antikorupsi dalam Kondisi Darurat Covid-19 di TK ABA Komplek Masjid Perak Prenggan - Suyadi Suyadi; Sumaryati Sumaryati; Trisna Sukmayadi; Waharjani Waharjani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The outbreak of corruption cases of COVID-19 funds from the Village, Regency to Ministry level, has direct implications for the death rate, especially early childhood, which reached 43.7% of total child deaths during the COVID-19 period or 0.85% of total deaths confirmed positive. Numeration and literacy as the minimum competencies of students have been widely discussed. However, literacy and numeracy specific to the field of anti-corruption have not been widely applied by both teachers and students. This Community Empowerment Program aims to increase the literacy and numeracy empowerment of partner groups through anti-corruption learning media innovation training. This PPM partner group is TK ABA Komplek Masjid Perak Kotagede Yogyakarta which consists of 20 teachers with undergraduate education. Data analysis techniques are used to measure the level of empowerment of partners in the anti-corruption literacy and numeracy fields. The Community Empowerment results show that improving anti-corruption literacy and numeracy competencies in children's stories have only reached the innovative and creative stages but have not yet reached digital technology-based. This is because online training during the Covid-19 era did not support interactive multimedia laboratories as literacy tools and children's numeracy stories based on digital technology. Community Empowerment Program results have changed the learning of anti-corruption literacy and numeracy during the COVID-19 pandemic to be more enjoyable to reduce the risk of stress and anxiety in children and increase immunity.